Metody nauczania jako systemy twierdzeń projektujących i jako systemy czynności dydaktycznych = Teaching methods as systems of projecting theorems and as systems of didactic activities - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the present paper the author has proved the thesis that the methods of teaching should be discussed from two points of view, that is to say: a) from the view-point of the knowledge of methods - then the method constitutes the system of so called projecting theorems and their stylystic variants called the didactic directions; b) from the view-point of methods as systems of didactic activities. The author also classifies the teaching methods according to the geneticcriterion and according to the teleological criterion.
Keywords: nauczanie; metoda